Journeys : resilience and growth for survivors of intimate partner abuse - Miller, Susan L. (Gender and justice (University of California Press), 2018)
"More than one in three women in the United States has experienced rape, physical violence, or stalking by an intimate partner in their lifetime. Luckily, many are able to escape this life--but what happens to them after? Journeys focuses on the desperately understudied topic of the resiliency of long-term (over 5 years) survivors of intimate partner violence and abuse. Drawing on participant observation research and interviews with women years after the end of their abusive relationships, author Susan L. Miller shares these women's trials and tribulations, and expounds on the factors that facilitated these women's success in gaining inner strength and personal transformation. Written for researchers, practitioners, and policy makers in criminal justice, sociology, and social services, Journeys shares stories that hope to inspire other victims and survivors while illuminating the different paths to resiliency and growth"--Provided by publisher.